Internalisasi Nilai Pendidikan Islam dan Habit Information pada Anak Berkebutuhan Khusus di Tangerang Selatan - Wari Setiawan (JURNAL INDO-ISLAMIKA, 2017)
This paper describes an internalization in teaching and learning among a group of the disabled children in South Tangerang as a psychological process. Here, they are involved in teaching and learning activities about the Islamic values that they undertak. Meanwhile, their teachers focus on developing their personal characteristics. This paper argues that the teachers, who teach them through this process, will successfully lead them to act according to the values of Islam that the teachers convey.